UNBELIEVERS’ MENTAL MODEL AND BEHAVIOURAL DISORDERS BASED ON THEIR QUERIES IN THE ALBAQARAH CHAPTER - Sempo, Muhammad Widus; Norwawi, Norita Binti Md; Haddade, Hasyim; Islam, Yousuf Mahbubul; Hasyim, Noorhayati Binti (Jurnal Adabiyah, 2020)
Unbelievers historically are the people who rejected the message of Allah revealed to His Prophet Muhammad (Peace be upon Him). The Prophet Muhammad is the Messenger of Allah who fights against idolaters and unbelievers. However, they kept denying the message of Islam and slandering the Prophet Muhammad SAW in many ways they can do. Instead of fully accepting Islam, they rejected the Prophet Muhammad’s teaching and caused both physical and psychological torture. The Prophet Muhammad felt hurt due to the mockery and their fabricated question to ridicule him indirectly. Thus, it is very significant to know the character of unbelievers, who they are actually, through analyzing their questions in the al-Baqarah chapter. This study relies on descriptive quantitative methods through the collection of verses related to the question of unbelievers to the prophet Muhammad in the al-Baqarah chapter. The study found that unbelievers went astray indicated by the purpose of their questions, which is not for the sake of truth, but to mock the Prophet Muhammad or to look for his fault. So, their question were sometimes illogical, and driven by stubbornness and self-conceit. الكافرون هم الذين حاربوا رسالة الإسلام التي جاء بها الرسول المصطفى محمد صلى الله عليه وسلم الذي أرسل لإزاحة الشرك والكفر على وجه الأرض. وهؤلاء الكافرون كانوا يرفضون هداية الإسلام ويزدرون بالنبي عليه الصلاة والسلام، فهم ينكرون دعوته الحق ويحاولون بكل الطرق الفتك به. وقد أثر ذلك في الرسول عليه الصلاة والسلام، ولا سيما افتراءاتهم التي كانوا يلفقهونها استهزاء به. وبناء عليه، فإن هذا البحث في معدنه يتقصى حقيقة نفس الكفرة وأخلاقهم الرذيلة من خلال أسئلتهم في سورة البقرة. والبحث يعتمد على قاعدة التحليل التي أجريت على الآيات القرآنية ألتي أوردت أسئلة الكفرة. ومن نتائج هذا البحث أن الكفرة هم أضل الناس سبيلا، وذلك لاستهزائهم بالرسول عليه الصلاة والسلام وتوقعهم الأخطاء من جانبه عليله الصلاة والسلام. فإن أسئلتهم كان أكثرهم ينافي المنطق والعقل السليم تعظمًا واستكبارًا. Orang-orang kafir adalah mereka yang menolak risalah Allah SWT melalui Nabi Muhammad SAW yang diutus untuk memerangi kemusyrikan dan kekufuran. Oleh itu, mereka sentiasa menolak hidayah Islam dan memfitnah baginda Nabi SAW secara berterusan. Mereka turut menafikan kebenaran dakwah baginda Nabi SAW dan juga menyiksa baginda sama ada secara fizikal mahupun psikologi. Perasaan baginda Nabi Muhammad terluka karena makian ataupun mereka yang sengaja dibuat-buat untuk untuk mengejek baginda. Oleh itu, artikel ini menyoroti mental dan tingkah laku buruk orang-orang kafir melalui ayat-ayat pertanyaan yang dilontarkan oleh mereka dalam surah al-Baqarah. Kajian ini menggunakan kaedah kuantitatif deskriptif melalui pengumpulan ayat-ayat tanya oleh orang-orang kafir dalam surah al-Baqarah. Sebagai kesimpulan, orang-orang kafir adalah kumpulan yang sesat dimana pertanyaan mereka bukan untuk mencari kebenaran. Justeru, mereka berpura-pura bertanya untuk menghina baginda Nabi SAW atau mencari kesalahannya. Pertanyaan mereka kebanyakannya adalah tidak logik, bahkan petanyaan mereka mencerminkan sifat angkuh dan ujub.